Self-adhesive lithium adsorbent as well as preparation method and application thereof

Through the bonding system of catechol and polyamine interfacial agents, the problem of insufficient adsorption performance of lithium adsorbents during use is solved, and an efficient self-adhesive lithium adsorbent is prepared, suitable for a variety of lithium Resource extraction scenarios improve adsorption performance and anti-soluble loss performance.

CN119114037APending Publication Date: 2024-12-13WANHUA CHEM GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411556241.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

During the use of the existing lithium adsorbent, there are problems in which the powder adsorbent is embedded by the adhesive and the exposure rate of the active adsorption site is reduced, resulting in the failure to fully exert the adsorption performance, which limits its application in brine lithium extraction.

Method used

The self-adhesive lithium adsorbent is prepared by using catechol and polyamine interfacial agents as the bonding system of lithium adsorbents through standstill reaction and granulation process, and the catechol interfacial agent and lithium adsorbent precursor powder are used. The multiple interactions with polyamine-based interface additives enhance the cohesion of lithium adsorbents, and accelerate the bonding reaction rate through the metal ion/oxidant system, reduce the amount of adhesive, and improve adsorption performance.

Benefits of technology

It significantly improves the adsorption performance and anti-soluble properties of lithium adsorbents, reduces the wrapping of adsorbent precursor powder by the adhesive, improves the adsorption, desorption amount and brine ion mass transfer rate, and is suitable for lithium extraction in salt lakes, Scenarios such as recovery of lithium deposited mother liquor and extraction of lithium in oil well brine.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005116517060000101
    Figure BDA0005116517060000101
  • Figure BDA0005116517060000102
    Figure BDA0005116517060000102
  • Figure BDA0005116517060000111
    Figure BDA0005116517060000111
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium adsorbents, and discloses a self-adhesive lithium adsorbent as well as a preparation method and application thereof, and the self-adhesive lithium adsorbent comprises the following components in percentage by total weight of the lithium adsorbent: 85wt%-99wt% of lithium adsorbent precursor powder, 0.2 wt%-12wt% of a catechol interface agent and 0.2 wt%-12wt% of a polyamine interface aid. The lithium adsorbent is one or more of spherical particles, rod-shaped particles and irregular particles, and the average particle size is 0.5-2 mm; the saturated lithium adsorption capacity is 15-30 g / L; the solution loss rate is less than or equal to 0.01% / hundred cycles; and the wear rate is less than or equal to 0.1% / hundred cycles. The adsorption performance, the solution loss resistance and the abrasion resistance of the lithium adsorbent can be obviously improved, and the lithium adsorbent is particularly suitable for application scenes such as extraction of lithium from salt lake brine, recovery of lithium precipitation mother liquor, extraction of lithium from oil well brine and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium adsorbents, and in particular relates to a self-adhesive lithium adsorbent and a preparation method and application thereof. Background Art

[0002] Nearly 80% of my country's lithium resources are distributed in salt lakes in Qinghai and Tibet. Lithium extraction from salt lakes is one of the important sources of lithium resources. The adsorption method for lithium extraction has the advantages of high production efficiency, low extraction cost and low environmental pollution. Among them, lithium adsorbent is the key separation and purification material for lithium extraction by adsorption, and its adsorption performance directly determines the efficiency of lithium extraction. At present, in order to avoid the loss of powdered lithium adsorbent during use and the problem of excessive bed pressure drop, a process of mixing powdered lithium adsorbent with polymer adhesive for granulation is usually adopted to prepare granular lithium adsorbent.

[0003] Patent document CN102631897B discloses a method for preparing spherical particle lithium adsorption resin, which comprises mixing an inorganic lithium adsorbent precursor and a polymer material or a reactive monomer, a porogen, etc. to prepare a dispersed phase, and then stirring the dispersed phase to be "suspended" in a continuous phase to form beads and solidify them into spherical particle lithium adsorption resin.

[0004] Patent document CN115445587B discloses a method for preparing a high adsorption capacity adsorbent with a hollow composite multi-level pore structure. The method uses the principle of phase inversion to evenly mix inorganic powder with selective adsorption capacity with a polymer and a solvent in a certain proportion, then squeeze it into a coagulation bath and then pelletize it.

[0005] The lithium adsorbents prepared by the above schemes all have additional polymers added as powder binders, which inevitably lead to the problem that the powder adsorbents are embedded in the binders and the exposure rate of active adsorption sites is reduced, and the adsorption performance of the powder adsorbents is not fully utilized.

[0006] Patent document CN114433007B discloses a method for preparing lithium adsorbent by in-situ growth on Al2O3 balls, where aluminum-based adsorbent powder is grown on the pores or surface of Al2O3 balls, achieving the integration of effective component synthesis and effective component powder granulation, avoiding the cumbersome process of synthesizing lithium adsorbent powder first and then molding the lithium adsorbent powder. However, this solution is limited by the in-situ growth environment, the loading amount of the powder adsorbent is low, and the adsorption performance of the adsorbent is not significantly superior to that of the adsorbent prepared by the polymer binder mixed granulation process.

[0007] The above-mentioned problems existing in the preparation of lithium adsorbents restrict the application of lithium adsorbents in lithium extraction from brine. Therefore, it is necessary to develop new lithium adsorbents and granulation methods thereof to solve the problem of how to improve the adsorption performance of lithium adsorbents. Summary of the invention

[0008] The purpose of the present invention is to provide a self-adhesive lithium adsorbent in order to overcome the deficiencies in the prior art. The adsorption performance of the lithium adsorbent of the present invention is significantly improved, and it is particularly suitable for application scenarios such as lithium extraction from salt lakes, recovery of lithium precipitation mother liquor, and lithium extraction from oil well brine.

[0009] Another object of the present invention is to provide a method for preparing the lithium adsorbent.

[0010] Another object of the present invention is to provide application of the lithium adsorbent.

[0011] In order to achieve the above invention object, the present invention provides the following technical solutions:

[0012] In a first aspect, a self-adhesive lithium adsorbent is provided, wherein the self-adhesive lithium adsorbent (in appearance) is one or more of spherical, rod-shaped, and irregular particles, and has an average particle size of 0.5 to 2 mm (e.g., 0.5 mm, 1 mm, 1.5 mm, 2 mm);

[0013] The saturated lithium adsorption capacity of the lithium adsorbent is 15 to 30 g / L (for example, 15 g / L, 20 g / L, 25 g / L, 30 g / L); the dissolution rate is ≤0.01% / 100 cycles (for example, 0.005% / 100 cycles, 0.001% / 100 cycles); and the wear rate is ≤0.1% / 100 cycles (for example, 0.05% / 100 cycles, 0.01% / 100 cycles, 0.005% / 100 cycles, 0.001% / 100 cycles).

[0014] According to the self-adhesive lithium adsorbent provided by the present invention, in some embodiments, the self-adhesive lithium adsorbent comprises: lithium adsorbent precursor powder, catechol interface agent and polyamine interface additive; based on the total weight of the lithium adsorbent as 100wt%, wherein:

[0015] The content of the lithium adsorbent precursor powder is 85wt% to 99wt% (e.g., 85wt%, 90wt%, 95wt%, 99wt%),

[0016] The content of the catechol surfactant is 0.2wt% to 12wt% (for example, 0.2wt%, 1wt%, 5wt%, 10wt%, 12wt%),

[0017] The content of the polyamine interface additive is 0.2 wt% to 12 wt% (for example, 0.2 wt%, 1 wt%, 5 wt%, 10 wt%, 12 wt%).

[0018] In the text, the lithium adsorbent precursor powder refers to an adsorbent powder with the general formula LiCl·mAl(OH)3·nH2O, wherein m=2~3, n=2~4; the lithium adsorbent precursor powder has a particle size of 0.5~10μm, for example, 0.5μm, 1μm, 3μm, 5μm, 8μm, 10μm, etc.

[0019] Wherein, the catechol interface agent is selected from the group containing catechol group organic matter and its derivatives, wherein the R group is, for example, an alkyl group, an aryl group and its derivatives, such as a substituted alkyl group, a substituted aryl group, etc., preferably one or more of catechol, DOPA (3,4-dihydroxyphenylalanine), dopamine (2-(3,4-dihydroxyphenyl)ethylamine), tannic acid, urushiol, and tea polyphenols.

[0020] Wherein, the polyamine interface additive is selected from polyethyleneimine The degree of polymerization thereof is 10 to 50 (eg, 10, 15, 25, 35, 50).

[0021] The mass ratio of the catechol interface agent to the polyamine interface additive can be 4:1 to 1:4 (for example, 4:1, 2:1, 1:1, 1:2, 1:4); the sum of the masses of the catechol interface agent and the polyamine interface additive accounts for 1wt% to 15wt% (for example, 1wt%, 5wt%, 10wt%, 15wt%) of the total mass of the self-adhesive lithium adsorbent.

[0022] In a second aspect, a method for preparing the aforementioned self-adhesive lithium adsorbent is provided, comprising the following steps:

[0023] 1) mixing lithium adsorbent precursor powder, catechol interface agent, polyamine interface additive and buffer uniformly, and allowing to react to obtain a bonding precursor;

[0024] 2) The bonding precursor in step 1) is mixed with a bonding promoter, granulated, and washed with water to obtain a self-bonding lithium adsorbent.

[0025] According to the preparation method of the present invention, the self-adhesive lithium adsorbent (appearance) obtained is one or more of spherical, rod-shaped, and irregular particles, with an average particle size of 0.5 to 2 mm (for example, 0.5 mm, 1 mm, 1.5 mm, 2 mm); its saturated lithium adsorption capacity is 15 to 30 g / L (for example, 15 g / L, 20 g / L, 25 g / L, 30 g / L); the dissolution rate is ≤0.01% / hundred cycles (for example, 0.005% / hundred cycles, 0.001% / hundred cycles); the wear rate is ≤0.1% / hundred cycles (for example, 0.05% / hundred cycles, 0.01% / hundred cycles, 0.005% / hundred cycles, 0.001% / hundred cycles).

[0026] According to the preparation method of the present invention, the self-adhesive lithium adsorbent prepared therefrom comprises: lithium adsorbent precursor powder, catechol interface agent and polyamine interface additive; based on the total weight of the lithium adsorbent as 100wt%, wherein:

[0027] The content of lithium adsorbent precursor powder is 85wt% to 99wt% (for example, 85wt%, 90wt%, 95wt%, 99wt%), the content of catechol interface agent is 0.2wt% to 12wt% (for example, 0.2wt%, 1wt%, 5wt%, 10wt%, 12wt%), and the content of polyamine interface additive is 0.2wt% to 12wt% (for example, 0.2wt%, 1wt%, 5wt%, 10wt%, 12wt%).

[0028] According to the preparation method provided by the present invention, in some embodiments, the lithium adsorbent precursor powder refers to an adsorbent powder with the general formula LiCl·mAl(OH)3·nH2O, wherein m=2-3, n=2-4; the lithium adsorbent precursor powder has a particle size of 0.5-10 μm (for example, 0.5 μm, 1 μm, 5 μm, 10 μm).

[0029] In the text, the lithium adsorbent precursor powder can be obtained by, for example, mixing a lithium salt (such as LiCl), an aluminum salt (such as AlCl3), and an alkali (such as NaOH) in an aqueous solution for co-precipitation reaction, or by referring to the methods disclosed in the literature (Wu Zhijian et al., Mechanism of lithium adsorption from brine by aluminum hydroxide-based lithium adsorbent, Salt Lake Research, 2018, 26(3)) and patents (such as CN106076243A). The specific preparation process will not be repeated in this invention.

[0030] In order to meet the requirements of the present invention for the particle size of the lithium adsorbent precursor powder, it may be necessary to go through steps such as pulverization and screening, which can be performed using conventional methods in the art.

[0031] In some embodiments, the catechol-based interfacial agent is selected from organic matter and its derivatives, wherein the R group is an alkyl group, an aryl group and its derivatives, preferably one or more of catechol, dopa (3,4-dihydroxyphenylalanine), dopamine (2-(3,4-dihydroxyphenyl)ethylamine), tannic acid, urushiol and tea polyphenols.

[0032] In some embodiments, the polyamine interface additive is selected from polyethyleneimine The degree of polymerization thereof is 10 to 50 (eg, 10, 15, 25, 35, 50).

[0033] In some embodiments, the mass ratio of the catechol-based interfacial agent to the polyamine-based interfacial additive may be 4:1 to 1:4 (eg, 4:1, 2:1, 1:1, 1:2, 1:4).

[0034] In some embodiments, the buffer is a tris(hydroxymethyl)aminomethane hydrochloride) (Tris) aqueous solution with a molar concentration of 40-60 mmol / L and a buffer pH of 8-9.

[0035] In some embodiments, the total weight of the lithium adsorbent precursor powder, the catechol-based interface agent, the polyamine-based interface aid and the buffer is 100 wt%, wherein:

[0036] The content of the lithium adsorbent precursor powder is 60wt% to 89wt% (e.g., 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, 89wt%);

[0037] The content of the catechol surfactant is 0.1wt% to 11wt% (e.g., 0.1wt%, 1wt%, 5wt%, 10wt%, 11wt%);

[0038] The content of the polyamine interface additive is 0.1wt% to 11wt% (for example, 0.1wt%, 1wt%, 5wt%, 10wt%, 11wt%);

[0039] The content of the buffer is 10 wt% to 30 wt% (eg, 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%).

[0040] In some embodiments, the static reaction in step 1) is to place the uniformly mixed lithium adsorbent precursor powder, catechol interfacial agent, polyamine interfacial additive and buffer in an air environment, and react at 15-30°C (for example, 15°C, 20°C, 25°C, 30°C) for 10-60min (for example, 10min, 20min, 30min, 40min, 50min, 60min) to obtain a bonding precursor in a paste, slurry or dough state.

[0041] In some embodiments, the adhesion promoter is selected from an aqueous solution of metal ions / oxidants, wherein the metal ions are preferably Cu 2+ , Fe 3+ 、Co 3+ 、Ni 2+One or more of, with a molar concentration of 1-20mmol / L (e.g., 1mmol / L, 5mmol / L, 10mmol / L, 15mmol / L, 20mmol / L); the oxidant is preferably one or more of hydrogen peroxide, sodium persulfate, potassium persulfate, and ozone, with a molar concentration of 5-50mmol / L (e.g., 5mmol / L, 10mmol / L, 20mmol / L, 25mmol / L, 30mmol / L, 40mmol / L, 50mmol / L).

[0042] In some embodiments, in step 2), the mass ratio of the bonding precursor to the bonding promoter is 100:1 to 1000:1, for example, 100:1, 300:1, 500:1, 800:1, 1000:1, etc.

[0043] In some embodiments, the mixing reaction in step 2) is to place the uniformly mixed bonding precursor and bonding promoter in an air environment and react for 5-60 minutes (for example, 5 minutes, 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, 60 minutes) at 15-30°C (for example, 15°C, 20°C, 25°C, 30°C). The reaction can be carried out in a mixing device or a granulating device.

[0044] In the present invention, the process of mixing the lithium adsorbent precursor powder, catechol interface agent, polyamine interface aid and buffer, and the bonding precursor and bonding promoter in steps 1 and 2) can be carried out using conventional equipment in the art (such as mechanical stirring, kneading machine, planetary mixer, screw mixer, etc.); the bonding precursor and bonding promoter in step 2) can be mixed and granulated using conventional equipment in the art such as crushing granulator, planetary extruder-spheronizer, screw extruder-granulator, spray granulator, etc. The mixing and granulation process is carried out using conventional means in the art, and the present invention has no special requirements; the water washing step in step 2) can be carried out using conventional methods in the art. It is known to those skilled in the art that the above mixing, granulation, and water washing steps do not affect the inherent properties of the lithium adsorbent.

[0045] In another aspect of the present invention, the application of the aforementioned self-adhesive lithium adsorbent in extracting lithium ions from brine (especially salt lake brine) can be achieved by conventional processes and conventional equipment in the art, which will not be described in detail here.

[0046] The present invention adopts catechol and polyamine substances as the bonding system of lithium adsorbent. On the one hand, the catechol interfacial agent contains catechol groups, which can have multiple chemical or physical interactions with lithium adsorbent precursor powder and polyamine interfacial additives, including hydrogen bonds, metal-catechol coordination bonds, π-π interactions, π-cation interactions, oxidative crosslinking and electrostatic interactions, etc. Only a small amount of catechol-polyamine structure is needed to significantly enhance the cohesion of lithium adsorbent precursor powder in brine, ensure that the lithium adsorbent maintains structural integrity during long-term use, reduce the amount of adhesive, reduce the coating of the adsorbent precursor powder by the adhesive, so that more lithium adsorbent precursor powder can play a role in the adsorption-desorption process, and increase the adsorption and desorption amount of the lithium adsorbent.

[0047] On the other hand, the hydrophilic structure of catechols and polyamines also improves the dispersion of precursor powders in the adsorbent and reduces the agglomeration of powders. At the same time, hydrophilic adhesives are beneficial to increase the mass transfer rate of brine ions in the adsorbent during adsorption and desorption, further improving the adsorption performance of the adsorbent.

[0048] In addition, the present invention adopts a metal ion / oxidant system as an adhesion promoter, and accelerates the reaction rate of the catechol-polyamine structure through the catalytic effect of the metal ions and the oxidant, thereby significantly improving the adhesion speed and overcoming the problem of the slow reaction rate of the catechol-polyamine.

[0049] Compared with the prior art, the beneficial effects of the present invention are at least:

[0050] (1) The catechol-polyamine adhesive system is used. Through the multiple interactions between the adhesive and the powder, only a small amount of adhesive is needed to ensure that the lithium adsorbent maintains structural integrity during long-term use, and the adsorbent dissolution rate and wear rate are extremely low;

[0051] (2) The amount of adhesive used is small, which reduces the adhesive's wrapping of the adsorbent precursor powder and increases the adsorption and desorption amount of the lithium adsorbent;

[0052] (3) The hydrophilic structure of catechols and polyamines reduces the agglomeration of powders inside the adsorbent, increases the mass transfer rate of brine ions in the adsorbent during adsorption and desorption, and improves the adsorption performance of the adsorbent.

[0053] Based on the above beneficial effects, the adsorption performance, anti-dissolution performance and wear resistance of the lithium adsorbent prepared by the method of the present invention can be significantly improved, and it is particularly suitable for application scenarios such as lithium extraction from salt lake brine, recovery of lithium precipitation mother liquor, and lithium extraction from oil well brine. DETAILED DESCRIPTION

[0054] In order to understand the technical features and content of the present invention in detail, the preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described in the embodiments, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. For those who do not specify specific conditions in the embodiments, they are carried out according to normal conditions or the conditions recommended by the manufacturer.

[0055] <Source of raw materials>

[0056] The raw materials used in the following examples and comparative examples were all purchased from Inokai.

[0057] Instrument information used in the examples:

[0058] The particle sizes of lithium adsorbent precursor powder and lithium adsorbent were measured by an image particle size analyzer (Dandong Biotech BT-2900); the lithium ion concentration in the saturated lithium adsorption test and the aluminum ion concentration in the adsorbent dissolution rate test were measured by inductively coupled plasma emission spectrometer (Agilent 720-OES).

[0059] <Performance Test>

[0060] (1) Test of saturated lithium adsorption capacity of adsorbent: 5.0 mL of the adsorbent to be tested was placed in 500 mL of brine (lithium content of brine ~500 mg / L, magnesium content ~10000 mg / L), and adsorbed by oscillation for 16 h. The lithium ion content in the brine before and after adsorption was measured respectively. The saturated lithium adsorption capacity of the adsorbent was calculated according to the following formula:

[0061]

[0062] in:

[0063] Q——saturated lithium adsorption capacity of adsorbent, g / L;

[0064] C0——Lithium ion content in brine before adsorption, g / L;

[0065] C A ——Lithium ion content in brine after adsorption, g / L;

[0066] V B ——Brine volume, i.e. 500mL;

[0067] V A ——adsorbent volume, i.e. 5.0 mL;

[0068] (2) Test of adsorbent dissolution rate: 50 mL of the adsorbent to be tested was taken, weighed and loaded into the column. Brine was passed through the adsorbent bed in the column at a flow rate of 4 BV / h and adsorbed for 4 h. The column was washed with water for 10 min. Water was used as the desorption liquid and desorbed at a flow rate of 2 BV / h for 2 h. The aluminum ion concentration in the desorption liquid was measured. This operation was repeated for 100 cycles. The adsorbent dissolution rate was calculated according to the following formula:

[0069]

[0070] in:

[0071] D——dissolution rate of adsorbent, % / hundred cycles;

[0072] C Al ——Aluminum ion content in the desorption solution per cycle, g / mL;

[0073] V d ——The volume of desorption liquid per cycle, i.e. 2×50×2=200mL;

[0074] Σ——100-cycle accumulation;

[0075] m A ——Mass of adsorbent before adsorption, g;

[0076] M Al ——Mass fraction of aluminum in the adsorbent (calculated based on the composition and proportion of lithium adsorbent precursor powder in the adsorbent);

[0077] (3) Adsorbent wear rate test: Take 50 mL of the adsorbent to be tested, weigh it and load it into the column. Use the same conditions as the adsorbent dissolution rate test to test it and cycle it for 100 cycles. Take out the adsorbent and weigh it. The adsorbent wear rate is calculated according to the following formula:

[0078]

[0079] in:

[0080] A——wear rate of adsorbent, % / hundred cycles;

[0081] m0——mass of adsorbent before adsorption, g;

[0082] m 100 ——Mass of adsorbent after 100 adsorption cycles, g.

[0083] The main components of the Chaerhan Salt Lake brine used below are shown in Table 1.

[0084] Table 1 Main components of Chaerhan Salt Lake brine

[0085]

[0086] Example 1

[0087] LiCl, AlCl3, and NaOH were mixed in an aqueous solution for coprecipitation reaction, crushed and sieved to obtain a lithium adsorbent precursor powder (LiCl·2Al(OH)3·2H2O, particle size 5μm), which was mixed with dopamine, polyethyleneimine (polymerization degree 20) and Tris aqueous solution (concentration 50mmol / L, pH=8.5) in a kneader, wherein the content of each component was: lithium adsorbent precursor powder 60wt%, dopamine 5wt%, polyethyleneimine 5wt%, Tris aqueous solution 30wt%. After mixing evenly, it was placed in an air environment and reacted at 20°C for 30 minutes to obtain a paste-like adhesive precursor. The adhesive precursor was mixed with an adhesive promoter Cu 2+ / Hydrogen peroxide aqueous solution (Cu 2+ The mixture was mixed with a mixture of 10 mmol / L of sodium hydroxide and 20 mmol / L of hydrogen peroxide (concentration 10 mmol / L, hydrogen peroxide concentration 20 mmol / L) and the mass ratio of the bonding precursor to the bonding promoter was 500:1. After uniform mixing, the mixture was placed in an air environment and reacted for 10 min at 20 ° C in a planetary extruder-spheronizer. After granulation and washing, a self-adhesive lithium adsorbent was obtained. The self-adhesive lithium adsorbent was spherical with an average particle size of 0.7 mm. The content of the lithium adsorbent precursor powder was 85 wt%, the content of the catechol interface agent was 7.5 wt%, and the content of the polyamine interface additive was 7.5 wt%. The saturated lithium adsorption capacity was 30 g / L, the dissolution rate was 0.005% / 100 cycles, and the wear rate was 0.01% / 100 cycles when tested with the old brine of the Chaerhan Salt Lake.

[0088] Example 2

[0089] LiCl, AlCl3, and NaOH are mixed in an aqueous solution for coprecipitation reaction, crushed, and sieved to obtain a lithium adsorbent precursor powder (LiCl·3Al(OH)3·4H2O, particle size of 10μm), which is mixed with catechol, polyethyleneimine (polymerization degree 50) and Tris aqueous solution (concentration 40mmol / L, pH=8) in a kneader, wherein the content of each component is: lithium adsorbent precursor powder 89wt%, catechol 0.2wt%, polyethyleneimine 0.8wt%, Tris aqueous solution 10wt%. After mixing evenly, it is placed in an air environment and reacted at 30°C for 60min to obtain a paste-like adhesive precursor. The adhesive precursor is mixed with an adhesive promoter Fe 3+ / Sodium persulfate aqueous solution (Fe 3+The mixture was mixed with a mixture of 20 mmol / L sodium persulfate (20 mmol / L sodium persulfate concentration, 50 mmol / L sodium persulfate concentration) in a kneader, and the mass ratio of the bonding precursor to the bonding promoter was 100:1. After uniform mixing, the mixture was placed in an air environment, reacted at 30°C in a planetary extruder-spheronizer for 60 minutes, granulated, and washed to obtain a self-adhesive lithium adsorbent. The self-adhesive lithium adsorbent was in the shape of a rod, with an average particle size of 2 mm, a content of 99 wt% lithium adsorbent precursor powder, 0.2 wt% catechol interface agent, and 0.8 wt% polyamine interface additive. The saturated lithium adsorption capacity was 15 g / L, the dissolution rate was 0.01% / 100 cycles, and the wear rate was 0.1% / 100 cycles using the old brine of the Chaerhan Salt Lake.

[0090] Example 3

[0091] LiCl, AlCl3, and NaOH were mixed in an aqueous solution for coprecipitation reaction, crushed and sieved to obtain a lithium adsorbent precursor powder (LiCl·2Al(OH)3·2H2O, particle size 0.5μm), which was mixed with DOPA, polyethyleneimine (polymerization degree 10) and Tris aqueous solution (concentration 60mmol / L, pH=9) in a kneader, wherein the content of each component was: 69.5wt% lithium adsorbent precursor powder, 0.4wt% DOPA, 0.1wt% polyethyleneimine, 30wt% Tris aqueous solution. After mixing evenly, the mixture was placed in an air environment and reacted at 15°C for 10 minutes to obtain a paste-like adhesive precursor. The adhesive precursor was mixed with an adhesive promoter Co 3+ / Potassium persulfate aqueous solution (Co 3+ The mixture was mixed with a mixture of 1 mmol / L of potassium persulfate (concentration 1mmol / L, potassium persulfate concentration 5mmol / L) and the mass ratio of the bonding precursor to the bonding promoter was 1000:1. After uniform mixing, the mixture was placed in an air environment and reacted for 5 minutes at 15°C in a planetary extruder-spheronizer. After granulation and washing, a self-adhesive lithium adsorbent was obtained. The self-adhesive lithium adsorbent was in the form of irregular particles with an average particle size of 0.5mm. The content of the lithium adsorbent precursor powder was 99wt%, the content of the catechol interface agent was 0.8wt%, and the content of the polyamine interface additive was 0.2wt%. The saturated lithium adsorption capacity was 25g / L, the dissolution rate was 0.008% / 100 cycles, and the wear rate was 0.09% / 100 cycles when tested with the old brine of the Chaerhan Salt Lake.

[0092] Example 4

[0093] The lithium adsorbent precursor powder of Example 3 was mixed with tannic acid, polyethyleneimine (polymerization degree 30) and Tris aqueous solution (concentration 50mmol / L, pH=8.5) in a kneader, wherein the content of each component was: lithium adsorbent precursor powder 76wt%, tannic acid 11wt%, polyethyleneimine 3wt%, Tris aqueous solution 10wt%. After being mixed evenly, it was placed in an air environment and reacted at 15°C for 10 minutes to obtain a paste-like adhesive precursor. The adhesive precursor was mixed with an adhesive promoter Ni 2+ / Ozone aqueous solution (Ni 2+ The mixture was mixed with a mixture of 10 mmol / L of ozone (concentration 10 mmol / L, ozone concentration 50 mmol / L) and the mass ratio of the bonding precursor to the bonding promoter was 500:1. After uniform mixing, it was placed in an air environment and reacted for 5 minutes at 15°C in a planetary extruder-spheronizer. After granulation and washing, a self-adhesive lithium adsorbent was obtained. The self-adhesive lithium adsorbent was spherical with an average particle size of 1.0 mm. The content of the lithium adsorbent precursor powder was 85 wt%, the content of the catechol interface agent was 12 wt%, and the content of the polyamine interface additive was 3 wt%. The saturated lithium adsorption capacity was 20 g / L, the dissolution rate was 0.007% / 100 cycles, and the wear rate was 0.06% / 100 cycles when tested with the old brine of the Chaerhan Salt Lake.

[0094] Example 5

[0095] The lithium adsorbent precursor powder of Example 3 was mixed with urushiol, polyethyleneimine (polymerization degree 30) and Tris aqueous solution (concentration 50mmol / L, pH=8.5) in a kneader, wherein the content of each component was: lithium adsorbent precursor powder 76wt%, urushiol 3wt%, polyethyleneimine 11wt%, Tris aqueous solution 10wt%. After being mixed evenly, it was placed in an air environment and reacted at 15°C for 10 minutes to obtain a paste-like adhesive precursor. The adhesive precursor was mixed with an adhesive promoter Ni 2+ / Ozone aqueous solution (Ni 2+ The mixture was mixed with a mixture of 10 mmol / L of ozone (concentration 10 mmol / L, ozone concentration 50 mmol / L) and the mass ratio of the bonding precursor to the bonding promoter was 500:1. After uniform mixing, it was placed in an air environment and reacted for 5 minutes at 15 ° C in a planetary extruder-spheronizer. After granulation and washing, a self-adhesive lithium adsorbent was obtained. The self-adhesive lithium adsorbent was spherical with an average particle size of 1.0 mm. The content of the lithium adsorbent precursor powder was 85 wt%, the content of the catechol interface agent was 3 wt%, and the content of the polyamine interface additive was 12 wt%. The saturated lithium adsorption capacity was 22 g / L, the dissolution rate was 0.005% / 100 cycles, and the wear rate was 0.03% / 100 cycles when tested with the old brine of the Chaerhan Salt Lake.

[0096] Example 6

[0097] The lithium adsorbent precursor powder of Example 3 was mixed with tea polyphenol, polyethyleneimine (polymerization degree 30) and Tris aqueous solution (concentration 50mmol / L, pH=8.5) in a kneader, wherein the content of each component was: lithium adsorbent precursor powder 69.5wt%, urushiol 0.1wt%, polyethyleneimine 0.4wt%, Tris aqueous solution 30wt%. After being mixed evenly, it was placed in an air environment and reacted at 15°C for 10 minutes to obtain a paste-like adhesive precursor. The adhesive precursor was mixed with an adhesive promoter Ni 2+ / Ozone aqueous solution (Ni 2+ The mixture was mixed with a mixture of 10 mmol / L of ozone (concentration 10 mmol / L, ozone concentration 50 mmol / L) and the mass ratio of the bonding precursor to the bonding promoter was 500:1. After uniform mixing, the mixture was placed in an air environment and reacted for 5 minutes at 15°C in a planetary extruder-spheronizer. After granulation and washing, a self-adhesive lithium adsorbent was obtained. The self-adhesive lithium adsorbent was spherical with an average particle size of 1.0 mm. The content of the lithium adsorbent precursor powder was 99 wt%, the content of the catechol interface agent was 0.2 wt%, and the content of the polyamine interface additive was 0.8 wt%. The saturated lithium adsorption capacity was 18 g / L, the dissolution rate was 0.01% / 100 cycles, and the wear rate was 0.1% / 100 cycles when tested with the old brine of the Chaerhan Salt Lake.

[0098] Comparative Example 1

[0099] The lithium adsorbent precursor powder of Example 1 was mixed with a polymer adhesive polyvinyl chloride (PVC, Mn=80,000) and a solvent dichloromethane in a kneader, wherein the content of each component was: 60wt% of lithium adsorbent precursor powder, 10wt% of polyvinyl chloride, and 30wt% of dichloromethane. After uniform mixing, a pasty adhesive precursor was obtained. The adhesive precursor was granulated and washed with water in a planetary extruder-spheronizer to obtain a lithium adsorbent. The lithium adsorbent was spherical with an average particle size of 0.7mm. It was tested with the old brine of the Chaerhan Salt Lake, and the saturated lithium adsorption capacity was 6g / L, the dissolution rate was 0.05% / 100 cycles, and the wear rate was 0.5% / 100 cycles.

[0100] Comparative Example 2

[0101] The lithium adsorbent precursor powder of Example 1 was mixed with dopamine and Tris aqueous solution (concentration 50mmol / L, pH=8.5) in a kneader, wherein the content of each component was: 60wt% lithium adsorbent precursor powder, 10wt% dopamine, and 30wt% Tris aqueous solution. After being mixed evenly, it was placed in an air environment and reacted at 20°C for 30 minutes to obtain a paste-like adhesive precursor. The adhesive precursor was mixed with an adhesive promoter Cu 2+ / Hydrogen peroxide aqueous solution (Cu 2+The mixture was mixed in a kneader with a mass ratio of 500:1 (100:1). After uniform mixing, the mixture was placed in an air environment and reacted for 10 minutes at 20°C in a planetary extruder-spheronizer. After granulation and washing, a lithium adsorbent was obtained. The lithium adsorbent was spherical with an average particle size of 0.7 mm. The saturated lithium adsorption capacity was 10 g / L, the dissolution rate was 0.03% / 100 cycles, and the wear rate was 1% / 100 cycles when tested with the old brine of the Qarhan Salt Lake.

[0102] Comparative Example 3

[0103] The lithium adsorbent precursor powder of Example 1 was mixed with dopamine, polyethyleneimine (polymerization degree 20) and Tris aqueous solution (concentration 50mmol / L, pH=8.5) in a kneader, wherein the content of each component was: 60wt% lithium adsorbent precursor powder, 5wt% dopamine, 5wt% polyethyleneimine, and 30wt% Tris aqueous solution. After uniform mixing, it was placed in an air environment and reacted at 20°C for 30min to obtain a pasty bonding precursor. The bonding precursor was placed in an air environment and reacted at 20°C in a planetary extruder-spheronizer for 10min. The granulation requirements were not met and the particles that met the requirements could not be prepared. The reaction time was extended to 8h to meet the granulation requirements. After granulation and washing, a lithium adsorbent was obtained. The lithium adsorbent was spherical with an average particle size of 0.7mm. It was tested with the old brine of the Chaerhan Salt Lake. The saturated lithium adsorption capacity was 15g / L, the dissolution rate was 0.07% / hundred cycles, and the wear rate was 2% / hundred cycles.

[0104] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the spirit of the present invention.

Claims

1. A self-adhesive lithium adsorbent, characterized in that: The lithium adsorbent is in the form of one or more of spheres, rods, and irregular particles, with an average particle size of 0.5 to 2 mm, a saturated lithium adsorption capacity of 15 to 30 g / L, a dissolution rate of ≤0.01% / 100 cycles, and a wear rate of ≤0.1% / 100 cycles.

2. The self-adhesive lithium adsorbent according to claim 1, characterized in that The self-adhesive lithium adsorbent comprises lithium adsorbent precursor powder, a catechol interface agent and a polyamine interface additive; Preferably, based on the total weight of the lithium adsorbent, the content of the lithium adsorbent precursor powder is 85wt% to 99wt%, the content of the catechol interface agent is 0.2wt% to 12wt%, and the content of the polyamine interface additive is 0.2wt% to 12wt%.

3. The self-adhesive lithium adsorbent according to claim 2, characterized in that: The lithium adsorbent precursor powder refers to an adsorbent powder with a general formula of LiCl·mAl(OH)3·nH2O, wherein m=2-3, n=2-4; the particle size of the lithium adsorbent precursor powder is preferably 0.5-10 μm.

4. The self-adhesive lithium adsorbent according to claim 2, characterized in that: The catechol interfacial agent is selected from a group containing catechol The organic matter and its derivatives are preferably one or more of catechol, dopa (3,4-dihydroxyphenylalanine), dopamine (2-(3,4-dihydroxyphenyl)ethylamine), tannic acid, urushiol, and tea polyphenols.

5. The self-adhesive lithium adsorbent according to claim 2, characterized in that: The polyamine interface additive is selected from polyethyleneimine The degree of polymerization is 10-50.

6. A method for preparing the self-adhesive lithium adsorbent according to any one of claims 1 to 5, characterized in that: The steps include: 1) mixing lithium adsorbent precursor powder, catechol interface agent, polyamine interface additive and buffer uniformly, and allowing to react to obtain a bonding precursor; 2) The bonding precursor of step 1) is mixed with a bonding promoter, granulated, and washed with water to obtain a self-bonding lithium adsorbent.

7. The preparation method according to claim 6, characterized in that: The buffer is a tris(hydroxymethyl)aminomethane hydrochloride) (Tris) aqueous solution; preferably, the concentration of the buffer solution is 40-60 mmol / L, and the pH is 8-9; The adhesion promoter is selected from an aqueous solution of metal ions / oxidants, wherein the metal ions are preferably Cu 2+ , Fe 3+ 、Co 3+ 、Ni 2+ The oxidant is preferably one or more of hydrogen peroxide, sodium persulfate, potassium persulfate, and ozone; Preferably, the metal ion concentration in the aqueous solution of the adhesion promoter is 1 to 20 mmol / L, and the oxidant concentration is 5 to 50 mmol / L.

8. The preparation method according to claim 6, characterized in that: The content of lithium adsorbent precursor powder in the bonding precursor is 60wt% to 89wt%; the content of catechol interface agent is 0.1wt% to 11wt%; the content of polyamine interface auxiliary agent is 0.1wt% to 11wt%; the content of buffer is 10wt% to 30wt%; Preferably, the mass ratio of the catechol interface agent to the polyamine interface additive is 4:1 to 1:4; and / or The mass ratio of the bonding precursor to the bonding accelerator is 100:1 to 1000:

1.

9. The preparation method according to claim 6, characterized in that: The static reaction is to place the uniformly mixed lithium adsorbent precursor powder, catechol interface agent, polyamine interface aid and buffer in an air environment and react at 15-30° C. for 10-60 minutes; and / or The mixing reaction is to place the uniformly mixed bonding precursor and bonding accelerator in an air environment and react at 15-30° C. for 5-60 minutes.

10. Use of the self-adhesive lithium adsorbent according to any one of claims 1 to 5 or the self-adhesive lithium adsorbent prepared by the preparation method according to any one of claims 9 to 10 in extracting lithium ions from brine.